Investigating associations between maternal mental health on wheeze through two years of age in a South African birth cohort study - Macginty, Rae (Department of Public Health and Family Medicine, 2018)
Background: Wheezing is one of the most common respiratory illnesses in children worldwide. Severe wheeze can result in significant morbidity, caregiver burden and increased health care costs. In addition, early childhood wheeze may be associated with reduced lung function, diminished airway responsiveness, increased risk of asthma in late childhood and subsequent respiratory disease including asthma in adulthood. This is particularly true in those experiencing recurrent wheeze episodes, which in the presence of viral respiratory tract infections, are believed to lead to asthma diagnosis. Thus, it is imperative to understand the risk factors for early childhood wheeze to reduce the increasing burden of respiratory illness. Recent research has seen a shift to maternal psychosocial risk factors and the impact these have on child respiratory health outcomes, such as wheeze. Various studies, largely conducted in High Income Countries (HIC), have found associations between antenatal or postnatal psychosocial risk factors, such as depression, psychological distress, and Intimate Partner Violence (IPV), and child wheeze and/or asthma diagnosis in early stages of life. However, these studies predominantly considered those in low-income urban regions that were predisposed to respiratory illnesses, including wheeze and asthma. Utilising the techniques and knowledge gained from previous studies, this research considers the relationship between antenatal or postnatal maternal psychosocial exposures and the onset and recurrence of child wheeze in a South African setting. In the study population used for this research, the reported prevalence of antenatal psychological distress and depression was 23% and 20%, respectively, while 34% of the women were exposed to antenatal IPV. Often those suffering from poor mental health in these contexts are not recognised and therefore remain untreated. In addition, service provision in these settings is also generally poor. The combination of low levels of social and psychiatric support, with unique political and socio-economic risk factors, may result in more persistent and severe forms of psychosocial exposure in Low Middle Income Countries (LMIC). Given the high prevalence of psychosocial risk factors, as well as the high prevalence of child wheeze, South Africa provides an excellent platform to investigate the association between maternal antenatal or postnatal psychosocial exposure and the development and recurrence of child wheeze in an LMIC context. Methods: The data used for this research was provided by the Drakenstein Child Health Study (DCHS), a prospective birth cohort study conducted in the Drakenstein region, a peri-urban region outside of Paarl in the Western Cape of South Africa. Pregnant women over 18 years old, between 20-28 weeks' gestation, living in the region were enrolled in a parent study, in order to investigate the epidemiology and aetiology of respiratory illnesses in children. The parent study considered various risk factors, including psychosocial risk factors such as maternal depression, psychological distress and IPV, which were measured antenatally and postnatally by validated questionnaires. In the context of this research, wheeze was considered to be present if it was identified during any routine study follow-up visit, as well as at an unscheduled lower respiratory tract infection (LRTI) episode visit during the first two years of life. Recurrent wheeze was defined as experiencing two or more episodes of wheeze in a 12-month period. Logistic regression was used to investigate the relationship between antenatal and postnatal psychosocial risk factors and child wheeze. Results: From the results, postnatal psychological distress and IPV were associated with experiencing at least one episode of child wheeze (adjusted OR = 2.10, 95% CI: 1.16-3.79 and 1.60, 95% CI: 1.11-2.29 respectively) and recurrent wheeze (adjusted OR = 2.33, 95% CI: 1.09- 4.95 and 2.22, 95% CI: 1.35-3.63 respectively), within the first two years of life. No associations were found between antenatal psychosocial risk factors and child wheeze. Of clinical covariates explored, maternal smoking and household smoke exposure, birth weight, gestational age, sex and population group were associated with the presence of wheeze. All of these clinical covariates, as well as alcohol consumption were associated with recurrent child wheeze. Conclusion: Maternal postnatal psychological distress and postnatal IPV had the strongest impact on predicting wheeze outcomes. These findings suggest that screening and treatment programs which address maternal postnatal psychosocial risk factors may lessen the burden of childhood wheeze in LMIC settings.